1984
DOI: 10.1159/000260797
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Intraoral Demineralization Test

Abstract: Blocks of bovine enamel covered with a layer of Streptococcus mutans cells were mounted in specially-designed holders in a prosthesis and carried intraorally for 2 h. Measurements of the iodide permeability (Ip) of the blocks before and after intra-oral exposure showed an increase in Ip (+ΔIp), suggesting demineralization when the mouth was rinsed with a 10% sucrose solution at 0 and 60 min, but a decrease in Ip (––ΔIp), suggesting remineralization, after interoral exposure without rinsing. Repeated tests with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
6

Year Published

1986
1986
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 11 publications
0
45
0
6
Order By: Relevance
“…These models simulate the process of dental caries. 17,35 These models generally include all the multifactorial aspects of natural dental caries. That is a tooth substrate, either enamel or dentin; physiologically secreted saliva; the presence of dental plaque with cariogenic potential; a carbohydrate challenge (either experimentally controlled or provided by the subject's normal diet) and time, determined by the length of the experimental period.…”
Section: Use Of Plaque Ph Methods In the Development Of Therapeutic Amentioning
confidence: 99%
“…These models simulate the process of dental caries. 17,35 These models generally include all the multifactorial aspects of natural dental caries. That is a tooth substrate, either enamel or dentin; physiologically secreted saliva; the presence of dental plaque with cariogenic potential; a carbohydrate challenge (either experimentally controlled or provided by the subject's normal diet) and time, determined by the length of the experimental period.…”
Section: Use Of Plaque Ph Methods In the Development Of Therapeutic Amentioning
confidence: 99%
“…Four enamel blocks were covered with a layer of Streptococcus mutans IB 1600 and were mounted in a custom-made acrylic palatal appliance (2 blocks on each side), according to Brudevold et al [1984]. The appliance was worn in the mouth of a subject for 45 min, and the subject was given a rinse of 15 ml of 5% sucrose at the start of the experiment.…”
Section: Demineralizationmentioning
confidence: 99%
“…Demineralization has been studied in a number of laboratories and can be de tected by measurement of microhardness [Koulourides et al, 1974] or by microradiography and polar ized light microscopy of thin sections of enamel [Dijkman et al, 1986;ten Cate and Exterkate, 1986;Shellis and Poole, 1985;Featherstone et al, 1983]. Earlier studies in this laboratory demonstrated that the po rosity of enamel increases after exposure of enamel to acidic buffers and that this can be measured as an in crease in penetrability of the enamel to iodide ions [Bakhos and Brudevold, 1982], The iodide penetrabil ity (delta Ip) system has been adapted for use intraorally and has been utilized to follow the effects of ingesting metabolizable sugars either in the form of rinses or as solid foods [Kashket et al, 1988;Tehrani et al, 1986;Brudevold et al, 1984], However, correla tions have not been made between the increases in delta Ip and measurements, by the other means avail able, of mineral loss and possible changes in enamel ultrastructure. The present study was carried out in order to make these comparisons and, in addition, to examine the nature of the lesion that was formed un der the conditions of the intraoral cariogenicity test.…”
mentioning
confidence: 99%
“…Entretanto, a opção pelo uso do esmalte bovino não se baseou apenas em sua facilidade de obtenção. Diversos pesquisadores utilizam esse substrato para avaliar a desmineralização e remineralização 3,4,12,32,37,59,71,72,76,95,112 , porque ele apresenta um comportamento semelhante ao esmalte humano e uma menor variabilidade de resposta aos testes. KOULOURIDES; CHIEN 59 relataram não ter encontrado diferenças entre a cárie produzida nos dois tipos de esmalte quando utilizaram a microdureza para medi-la e concluíram que tanto o esmalte bovino quanto o humano podem ser usados nos estudos in situ.…”
Section: Diasunclassified
“…KOULOURIDES; CHIEN 59 relataram não ter encontrado diferenças entre a cárie produzida nos dois tipos de esmalte quando utilizaram a microdureza para medi-la e concluíram que tanto o esmalte bovino quanto o humano podem ser usados nos estudos in situ. Embora o esmalte humano seja considerado o substrato de escolha, ele apresenta maior variabilidade na composição e na resposta ao teste, devido à influências genéticas, diferenças na exposição ao flúor e idade 12,59,76,112 . Além disso, os dentes humanos apresentam coroa com tamanho menor e maior curvatura que os dentes bovinos, dificultando a obtenção de blocos adequados aos ensaios de microdureza 12,59,76,112 .…”
Section: Diasunclassified